Report on the practice in industry training in marine fisheries. - Mosqueda, Noel P. (College of Fisheries, University of the Philippines, 1964)
In the beginning God created the heavens and the earth; in the genesis He created man to have dominion over the fish of the sea and all the creatures that creep under, and all things beneath, and every living thing found in it's surrounding. All through the years since the beginning of time the sea has been man's only inspiration for his daily existence and happiness; it has been his source of hope and courage for the glorious moments that have yet to renew the lost friendship that the sea and man had once had witnessed only by the years gone by. And yet, from the very first day that man had cast his eye upon the unsurpassing beauty of the sea up to the present time when the sea has already had diverse and sundry changes, the sea still seems to man a mystery. For the sea yields amazing amount of shining jewels and precious stones and pearls not yet beholden by man, though all these priceless wealth of nature are found in untapped ocean depths and coral reefs still unexplored by man, man seems to have forgotten already that the sea also is a place where the fish abounds. Generations came, and went. The prediction that man would be as many as the sands in the sea and the stars in the sky came true. Society flourished; states were founded; castles that signified the hopes and dreams and ambitions of man were built upon the sand by innocent children, and they were destroyed when the tide came. Man dreamed dreams; they saw visions only to find themselves lost in a wilderness of an earnest desire to have a togetherness and intimacy with the fish that still dominates the sea. Politics became a byword in every emerging nation, and the fish was completely forgotten and abandoned. Though man still depended on the fish as a means for his daily living, it was regarded no more than a mere ingredient for his daily bread. Besides all this, it was a matter of time before he completely forgot the bounteous happiness that the fish could offer by just looking at it as it swims under the water amid the glimmering beam of the setting sun. In later times, population of man increased, each to its own way. Barbaric tribes, inhabited by savaged, rose into unexplored forests; sea-faring islanders raced their bancas against the furious winds going into places of no origin; young adventurers ventured into unknown shores, now in search for fish. The most anticipated moment had finally arrived wherein man would finally seek the lost intimacy that he should have shared with the fish before. Perhaps any fish-loving would come to pause and ask; from whence had come such a lifelong desire that man had for fish. This simple question has been asked times without number, and yet no man has been able to give a satisfying answer. This lifelong desire that man has for fish also comes from his utmost love for the sea. For as air is to the sea.